THE EFFECT OF POLITICAL CONNECTIONS, LEVEL OF GOVERNMENT OWNERSHIP, AND GOOD CORPORATE GOVERNANCE ON ANTI-CORRUPTION DISCLOSURE IN STATE-OWNED ENTERPRISES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2021-2024 - Dwi Damayanti Aghniyah; Eva Wany (International Journal of Accounting Innovation, 2026)
Objective : This study aims to examine and analyze the influence of political connections, government ownership levels, and Good Corporate Governance (GCG) on anti-corruption disclosure in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Method : Using a quantitative approach, the research population consists of 24 SOEs consistently listed on the IDX throughout the observation years. Data were analyzed using descriptive analysis and logistic regression. Results : The results of the study indicate that political connections have a significant positive effect on anti-corruption disclosure, suggesting that stronger political ties drive companies to enhance transparency to maintain legitimacy. Similarly, the level of government ownership was found to have a significant impact; companies with higher state ownership demonstrate a greater commitment to anti-corruption reporting to meet public accountability demands. Regarding Good Corporate Governance, the results are mixed: managerial and institutional ownership significantly influence anti-corruption disclosure, whereas the proportion of independent commissioners shows no significant effect. This indicates that the role of independent commissioners has not been fully effective in promoting anti-corruption transparency within Indonesian SOEs. Novelty : These findings provide insights for regulators and stakeholders to strengthen corporate oversight mechanisms and public sector integrity.